Threadneedle street meets Lombard street: Bagehot and central bankers in the aftermath of the great recession. Issue 6 (1st November 2020) - Carre, Emmanuel; Leloup, Sandrine
Abstract: The paper concerns the reception among central bankers of Bagehot's ideas on the lender of last resort (LLR). For the period 1999–2017 we construct a database of speeches by G7 central bankers that mention Bagehot. On the basis of this database, we show that there was a boom in mentions of Bagehot during the recent financial crisis. Using the Journal of Economic Literature (JEL) codes, we indicate that this increase in the references to Bagehot among central bankers mainly relates to the idea of the LLR, and specifically the so-called Bagehot rules. However, a variety of interpretations of these rules can be observed among central bankers. We argue that these differences in interpretation can be explained by the fact that Bagehot's rules are used by central bankers either to justify, or, on the contrary, to impose limits on the liquidity injections envisaged under the unconventional monetary policies adopted in reaction to the crisis. We conclude that these diverging preferences on liquidity injections among central bankers allow us to distinguish two main "types" of receptions of Bagehot's rules: liberal versus conservative.